The cost : Trump, China, and American revival - Bartiromo, Maria; Freeman, James, 1950- (Threshold Editions, 2020)
"The global markets editor at Fox Business Network and host of Sunday Morning Futures on Fox News highlights how Trump has been good for business, and his accomplishments so far and yet to come in that area"--